The impact of foreign trade liberalization on Albania’s economic growth: An econometrical approach - Dragusha, Blerta; Hasaj, Besarta; Kruja, Alba; Lulaj, Enkeleda (Journal of Eastern European and Central Asian Research (JEECAR), 2023)
The relationship between economic growth and foreign trade was put in focus by many economists when foreign trade developed. The case of Free Trade is always associated with significant positive effects on foreign trade and economic growth. This paper explains the relationship between trade liberalization, foreign trade, and economic growth in Albania using annual economic development data for 1994-2019. This study is based on hypotheses for Causality Testing concerning the cointegration between GDP and foreign trade, trade liberalization and GDP, and GDP and exports in Albania. The ordinary least squares (OLS) model has been used. Empirical results for the Albanian case show that trade liberalization has a positive relationship with economic growth, exports, and imports. However, the multiple regression proved that GDP, Openness Index, FDI, and remittances positively impacted trade volume growth.